Orf virus infection of human keratinocytes and dermal fibroblasts: Limited virus detection and interference with intercellular adhesion molecule‐1 up‐regulation. Issue 2 (29th January 2019) - Schneider, Laura E.; Protschka, Martina; Müller, Uwe; Muhsen, Mahmod; Magin, Thomas M.; Anderegg, Ulf; Saalbach, Anja; Büttner, Mathias; Alber, Gottfried; Siegemund, Sabine
Abstract: Orf virus (Parapoxvirus ovis, ORFV) is a dermatotropic virus causing pustular dermatitis in small ruminants and humans. We analysed isolated human primary keratinocytes (KC) and dermal fibroblasts (FB) for cell death and virus replication by infection with a patient‐derived ORFV isolate. ORFV infection was associated with rapid induction of cell death in KC allowing for considerable virus removal. Upon infection with ORFV, KC and FB harboured intracytoplasmic ORFV and showed viral protein presence; however, missing virus spread indicated an abortive infection. Upon ORFV exposure, KC but not FB secreted the pro‐inflammatory cytokine interleukin (IL)‐6. ORFV infection enhanced the frequency of KC expressing intercellular adhesion molecule (ICAM)‐1 which was independent of IL‐6. Interestingly, ORFV inhibited ICAM‐1 up‐regulation on infected but not on non‐infected KC. Even interferon‐γ, a potent inducer of ICAM‐1, up‐regulated ICAM‐1 only on non‐infected KC. Transfer of ORFV‐free supernatant from infected to non‐infected KC induced ICAM‐1 on non‐infected KC pointing to the involvement of soluble mediator(s). Similarly as in KC, in FB interference with ICAM‐1 up‐regulation by ORFV infection was also observed. In conclusion, we shed light on epidermal and dermal defense mechanisms to ORFV infection and point to a novel ICAM‐1‐related immune evasion mechanism of ORFV in human skin.